2016
DOI: 10.1007/s12975-016-0507-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Blood-Brain Barrier Disruption by an Apolipoprotein E-Mimetic Peptide Ameliorates Early Brain Injury in Experimental Subarachnoid Hemorrhage

Abstract: Apolipoprotein E (ApoE)-mimetic peptides have been demonstrated to be beneficial in secondary brain injury following experimental subarachnoid hemorrhage (SAH). However, the molecular mechanisms underlying these benefits in SAH models have not been clearly identified. This study investigated whether an ApoE-mimetic peptide affords neuroprotection in early brain injury (EBI) following SAH by attenuating BBB disruption. SAH was induced by an endovascular perforation in young, healthy, male wild-type (WT) C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…In experimental SAH, POSTN caused EBI or BBB disruption via the activation of mitogen-activated protein kinases (MAPKs) and matrix metalloproteinase (MMP)-9, interacting with another matricellular protein tenascin-C [13]. MAPKs and MMP-9 are well known to cause the degradation of cerebral microvessel basal lamina and tight junction protein zona occludens-1, resulting in BBB disruption and brain edema formation after SAH [31,32]. A more recent study also showed the possible involvement of POSTN in the development of EBI or BBB disruption after experimental SAH [28].…”
Section: Discussionmentioning
confidence: 99%
“…In experimental SAH, POSTN caused EBI or BBB disruption via the activation of mitogen-activated protein kinases (MAPKs) and matrix metalloproteinase (MMP)-9, interacting with another matricellular protein tenascin-C [13]. MAPKs and MMP-9 are well known to cause the degradation of cerebral microvessel basal lamina and tight junction protein zona occludens-1, resulting in BBB disruption and brain edema formation after SAH [31,32]. A more recent study also showed the possible involvement of POSTN in the development of EBI or BBB disruption after experimental SAH [28].…”
Section: Discussionmentioning
confidence: 99%
“…We further show that treatment with exogenous apoE mimetic peptides can partially replace endogenous apoE to decrease the BSCB permeability, thus reducing the anatomic and functional deficits in apoE deficient mice after SCI. Previous study show that delivery of exogenous apoE mimetic peptides is able to significantly decrease brain-blood-barrier (BBB) disruption and reduce the neuronal loss and functional deficits after subarachnoid hemorrhage (Pang et al, 2017). These studies suggest that exogenous apoE mimetic peptides could be a novel therapeutic agent to decrease the dysfunction of BSCB or BBB after SCI or other neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, APOE tends to maintain BBB integrity and promote neurological recovery. While APOE-deficiency provokes BBB dysfunction, exogenously administered APOE or its mimetic peptides preserve BBB integrity in experimental studies [197][198][199][200][201][202][203].…”
Section: The Bbb Integrity-promoting Effects Of Astrocytesmentioning
confidence: 99%